About Writing A Guide - Jeffrey, Robin (Open textbook library., 2016)
This writer's reference condenses and covers everything a beginning writing student should need to successfully compose college-level work. The book covers the basics of composition and revising, including how to build a strong thesis, how to peer review a fellow student's work, and a handy checklist for revision, before moving on to a broad overview of academic writing. Included for those students who need writing help at the most basic level are comprehensive sections on sentence style and grammar, verbs, nouns and other tenets of basic grammar. Finally, the sections on research and citation should help any student find solid evidence for their school work and cite it correctly, as well as encouraging an understanding of why citation is so important in the first place. This is a guide that is useful to writing students of all levels, either as a direct teaching tool or a simple reference.